Desain Grafis Peningkatan Kemampuan Multimedia Pada Remaja Desa Seantis - Diansyah, Tengku Mohd; Aulia, Rachmat; Siregar, Dodi (Jurnal TUNAS, 2019)
The theme in the implementation of community service activities is graphic design. Increasing the ability of multimedia in Saentis village adolescents in order to increase the ability of graphic design for youth in Seantis village. As the aim of this activity is to introduce, train and improve mosque skills in the IT field specifically in the field of graphic design through the design of banners or banners. This dedication supports the creation of young people who have talent and skills in the field of graphic design that can be used to get additional training with attractive designs such as printing business.